The functions and parameters of al-roznah in Omani architecture heritage - AL-Hudaifi, Wafa Awadh; Awang, Arita Hanim (Ithra Almarifah center for Conferences, Research, and Scientific Publishing., 2025)
The paper sheds light on the diversity of the use of the Al-Roznah as an essential element in Omani Architecture and its influential role in the functional aspect is clear as a source of lighting and ventilation of rooms by day and night, a place for cooking and a means of defence by pouring hot oils through the deep holes that are scattered in the Al-Roznah element. paper aims to reveal an aspect of interior design that has been overlooked in Omani architecture research. This paper aims to reveal an aspect of interior design that has been overlooked in Omani architecture research. The study will examine the importance of AL-Roznah and how the Omanis have designed it intelligently to meet their needs, and how it has formed a sober social lifestyle. the study relied on field visits in order to collect data accurately and illustrate it as well by taking measurements of the logs on average such as length, width and depth of the logs according to their location inside the house and their use. To provide a better understanding of the element of AL-Roznah in the old Omani house, the data was analysed by editing drawings and sketches using the AutoCAD program, as well as manually drawing the arches, the data was analysed based on what was observed in the field visits. A lot of data related to the types and uses of AL-Roznah inside the Omani house and the reasons for the difference in use and design. This study contributes to transferring the Omani concept of AL-Roznah in history, civilization and local architecture to future generations. This paper will provide comprehensive information to the concerned authorities about AL-Roznah that has not been documented before in previous research. It is a reference and a good destination for project owners interested in adding the AL-Roznah element to contemporary architecture in the future, as well as a basic addition to the literature of Omani architecture.